O fechamento de mina e a participação popular: da teoria à prática - Kelly Cristina Costa (2017)
Mining activity has several peculiarities, among them, the legal recognition of the environmental degradation it causes and the need for its recovery. The Brazilian mineral legislation in force is from the 1960s and, despite Bill 5,807 / 2013, also known as the Regulatory Framework of the Mineral Sector in discussion in the Chamber of Deputies, there is still a large legal gap, which leads to the executive power regulating the mining sector without legislation coming from the legislative power, mainly allowed by the National Department of Mineral Production (DNPM). Among the many standardized processes is the closure of mines, which involves all stages of deactivation of production, which includes measuring and mitigating associated impacts. In this process the participation of the directly affected population is fundamental, so that they do not only inherit negative impacts and the loss of the environmental patrimony. However, although the legal guidelines governing the plans highlight this participation, it is not known how (and if) it has occurred. Thus, this study aimed to evaluate how popular participation has been inserted in the processes associated to the closure of mines, both in theoretical and practical, that is, from the legal instruments and the reality experienced by areas that are inserted in the context. The general study was carried out based on theoretical and documentary researches, seeking to organize and relate the various legal instruments dealing with the topics "mine closure" and "popular participation". In the second part of the study, case studies were carried out, which involved the evaluation of social and economic transformations in two distinct mineral extraction areas, both in Minas Gerais, one with a scheduled shutdown and the other with adverse events was closed prematurely and suddenly. The results showed that on the theoretical level, although legislation is advanced, there are many overlaps and disconnections. The lack of guiding policy, the involvement of several institutions including public power, entrepreneurs and society are unfavorable elements to transpose what the law regulates and what reality presents. This is even clearer in the case studies, where it was observed that the closure has implied economic and landscape impacts of affected areas. In Mercês, Zona da Mata Mineira, there was the presentation of PAFEM. Due to the characteristics of mineral exploitation of bauxite, the extent of environmental influence, in the generation of employment, income and alteration of the landscape, this area was less dependent today than in the second area, located in the Quadrilátero Ferrífero, in the district of Antônio Pereira, municipality of Ouro Preto, where the absolute majority of city residents were linked and directly dependent on the mining enterprise. Overall, the study has shown that the challenges to effective popular participation and ensuring it has a voice in the mine closure process is still long but possible. This path involves the mobilization of society and the need for communities to feel a relation of belonging to the activity and not just subordinate to it.